Longitudinal Study of Violent Criminal Behavior in the United States, 1970-1984 - Megargee, Edwin I. ([Verlag nicht ermittelbar], 1996)
The primary objective of this project was to explore the familial, physical, psychological, social, and cultural antecedents and correlates of violent criminal offending. This research used an extensive longitudinal database collected on 1,345 young adult male offenders admitted to the Federal Correctional Institution (FCI) in Tallahassee, Florida, from November 3, 1970, to November 2, 1972. Using FBI arrest records ("rap sheets"), each inmate was classified on the basis of the National Crime Information Center Uniform Offense Codes into one of four distinct categories: (1) "angry violent," in which the apparent goal was to injure the victim, (2) "instrumentally violent," in which the aggressive behavior was a means to an end (as in a robbery), (3) "potentially violent," as evidenced by making threats or carrying weapons but in which the offender was not accused of any violent offenses, and (4) "nonviolent," in which the offender had not been charged with violent criminal behavior. Violent offenders were also subdivided into those who had been repetitively violent and those who had been charged with just one violent offense. As part of the classification process, each inmate was administered an extensive battery of tests by the research project staff. The two primary personality assessment instruments utilized were the Minnesota Multiphasic Personality Inventory (MMPI) and the California Psychological Inventory (CPI). Each inmate's caseworker filled out a series of of standard Bureau of Prisons forms recording the results of the medical, educational, and psychological evaluations, as well as salient aspects of the case and criminal history. The researchers also obtained copies of each offender's Presentence Investigation Report (PSI) that had been prepared by the federal probation officer, and then devised a series of scales to quantify the PSI data. In addition, an hour-long structured intake interview was administered to each inmate by his team psychologist. Global scales were constructed from these intake interviews. After each interview, the psychologists performed an evaluative Q-sort. Nine scales were later constructed based on these Q-sorts. Also, every dormitory officer and every work supervisor completed scales assessing each subject's interpersonal adjustment and work performance at 90-day intervals. Immediately prior to release, as many inmates as possible were reinterviewed and retested on the MMPI and the CPI. Follow-ups using FBI rap sheets were conducted in 1976 and 1984. Variables obtained from the Bureau of Prisons forms include age upon entry, race, marital status, age at first arrest, number of prior adult convictions, commitment offense(s), highest school grade completed, drug dependency, and alcoholism. Scales developed from the PSIs provide data on father, mother, and siblings, family incohesiveness, adequacy of childhood dwelling, social deviance of family, school problems, employment problems, achievement motivation, problems with interpersonal relations, authority conflicts, childhood and adolescent or adult maladjustment and deviance, poor physical health, juvenile conviction record, adult arrest and conviction record, violence of offense, group influence on illegal behavior, and prior prison adjustment. The intake interview inquired about the developmental family history and the child's development, the inmate's marriage, educational, and work history and attitudes, attitudes toward sex, military service and attitudes, self-reported use of alcohol and other substances, religious preferences and practices, and problems during any previous confinements. Scales based on the psychologists' Q-sorts evaluated aggression, hostility avoidance, authority conflict, sociability, social withdrawal, social/emotional constriction, passivity, dominance, and adaptation to the environment. Data are also provided on global dorm adjustment and the number of shots, cell house days, sick calls, and infractions for the offenders' first and second 90-day periods at the FCI.